Research, Design and Fabrication Microwave Modules of Receiver for NanoDragon satellite at S band - Thi Ha, Bui; Gia Duong, Bach (VNU Journal of Science: Mathematics - Physics; Vol 35 No 2DO - 10.25073/2588-1124/vnumap.4330, 2019)
Abstract: In the paper, the new microwave modules of NanoDragon satellite’s receiver were designed and fabricated. Purpose of this design is not only reduce budget but also respond to frequency requirement, bandwidth and transmission rate. The microwave modules consist of low noise amplifier (LNA), mixer and local oscillator (LO). These modules operate at S band according to requirement of satellite. Firstly, each module was designed, simulated, fabricated and measured. Then they were integrated together. Output of integrated microwave modules is IF signal with bandwidth is suitable for demodulation PCM – PM (BPSK). And have high gain value conform to receiver’s requirement. Simulation result of low noise amplifier is 19.108 dB at 2.9 GHZ. Simulation result of integrating two stage LNA become 2-stage LNA have gain value over 38 dB. Gain value obtained is 11.5 dB when measurement. Integrating microwave modules result is 10.5 dB with gain value. That mean this microwave modules of receiver operated very well. LNA was very good. This subsystem can apply for NanoDragon satellite’s receiver and receiver of ground station. Keywords: Receiver, Microwave Modules of Receiver, Satellite, NanoDragon satellite, LNA, Mixer, LO, IF. References [1] M.H. Jeaine, E.H. David, Design and Construction of a VHF Ground Station at San State University, Int.1.Engng Ed, 10 (5) (1994) 459-465. [2] G.M. Quinn, A New X–Band satellite Ground Station for Remote Sensing Application, 2003 Australian International Aerospace Conference, (2003) 66-71. [3] S.T. Tarun, G.O.Nathan, E.Z. Robert, Low cost ground station design for nanosatellite missions, 2006 AMSAT North American Space Symposium (2006) 128-132. [4] Y. Na, G. Li, Design of a Low Noise Amplifier of RF Communication Receiver for Minc, 2012 IEEE Symposium on Electrical & Electronics Engineering (2012) 80-85. [5] T.V. Hoi, B.G. Duong, Study and design of wide band low noise amplifier operating at C band, VNU Journal of Mathematics – Physics 29 (2) ( 2013) 16-24. [6] Sirenza Microdevices, SPF – 2086 Datasheet, https://www.datasheets360.com/part/detail/spf-2086/3729919505518703085/ [7] D.M. Pozar, Microwave Engineering, 3th Edition , John Wiley & Sons, Inc- New York, United State of America, 2005. [8] Linear Technology, LT5527 Datasheet, https://www.alldatasheet.com/datasheet-pdf/pdf/262180/LINER/LT5527.html